Entrepreneurial intention among Bangladeshi tourism students - Biswas, Chhanda (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis (UniMAP), 2017)
Link to publisher's homepage at http://ijbt.unimap.edu.my